Penentuan Prioritas Komoditas Unggulan Peternakan di Kabupaten Sumbawa Barat - Nursan, Muhammad; Septiadi, Dudi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
West Sumbawa Regency is one of the Regency in West Nusa Tenggara Province where the livestock subsector is one of the main livelihoods of its people. One of the efforts to increase the production and competitiveness of livestock commodities is by developing livestock commodities based on the priority of regional superior commodities. Therefore, the objectives of this study are (1) to determine the superior commodity of livestock commodity in West Sumbawa Regency, (2) to determine the priority of the superior commodity of livestock in West Sumbawa Regency. This research was conducted in West Sumbawa Regency. The data used in this study are secondary data and cross-section data obtained from the expert team of 7 people. The collected data is then analyzed using LQ and AHP methods. the results showed that the superior commodity of large livestock (ruminants), cattle was the leading commodity in 5 districts, buffalo was superior in 4 districts, sheep and horses were superior in 3 districts, and goats were the superior commodity in 2 districts. The superior commodity is poultry, broiler chicken is the superior commodity in 6 districts, free-range chicken and duck were superior in 3 districts and the commodity entok / goose and the pigeon is the superior commodity in 2 districts. Superior commodity of livestock which becomes priority in West Sumbawa Regency is based on the results of AHP analysis, cattle are livestock commodity with the first priority with a value of 0.267, followed by chickens with a value of 0.213, buffalo with a value of 0.194, goats with a value of 0.186 and finally a horse with a value of 0.141.